Analisis Tingkat Kegempaan Wilayah Jawa Timur berbasis Distribusi Spasial dan Temporal Magnitude Of Completeness (Mc), A-Value Dan B-Value - Chasanah, Uswatun; Handoyo, Eko (Department of Physics, Sebelas Maret University, 2021)
The Space and temporal distribution of the seismicity parameters consisting of magnitude of completeness (Mc), a-value, and b-value were estimated for the East Java, Indonesia using the International Seismological Center (ISC) earthquake catalogue. The main purposes of this research were to determine the parameters of the seismicity and its spatial temporal distribution so that early detection and warning systems in the East Java run optimally. All estimated parameters were analyzed based on an earthquake catalogue during 1980-2020 by applying The Maximum Curvature (MaxC) method. The MaxC method enumerate the highest value of the first subordinate of the cumulative Frequency Magnitude Distribution (FMD) graph. The value of the magnitude of completeness, which was estimated on this study as result Mc 3,4 – 4,8; a-value 5,560 - 8,244; and b-value (0,73 – 0,82 ± 0.13). The lower b-value (0,73 ± 0.13) was obtained for the southern part of the East Java. This area is indicated to have high seismic moment release and rock stress level accumulation. Understanding and clarifying the relation between seismicity parameters and structure of tectonic framework can guidance us to estimate seismic risk for earthquake hazard mitigation in the East Java.